2019
DOI: 10.1186/s40644-019-0277-6
|View full text |Cite
|
Sign up to set email alerts
|

Superb microvascular imaging technique in depicting vascularity in focal liver lesions: more hypervascular supply patterns were depicted in hepatocellular carcinoma

Abstract: PurposeTo investigate the capacity of Superb Microvascular Imaging (SMI) to detect microvascular details and to explore the different SMI features in various focal liver lesions (FLLs) and the correlation between SMI and microvessel density (MVD).Method: Eighty-three liver lesions were enrolled in our study, including 35 hepatocellular carcinomas (HCCs) and 48 non-HCCs. All patients underwent color Doppler flow imaging (CDFI) and SMI examination and were categorized into subgroups according to Adler semiquanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…These results are similar to previous studies which proved that power Doppler sonography was significantly successful in showing color signals in the residual portion of the tumors after treatment [13,14]. This also agrees with Tanaka, 2020 [14] who stated that power Doppler sonography was nearly equal to CT in showing tumor vascularity, as the color signals revealed by color or power Doppler sonography corresponded to the enhanced areas that were not ablated seen on CT.…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to previous studies which proved that power Doppler sonography was significantly successful in showing color signals in the residual portion of the tumors after treatment [13,14]. This also agrees with Tanaka, 2020 [14] who stated that power Doppler sonography was nearly equal to CT in showing tumor vascularity, as the color signals revealed by color or power Doppler sonography corresponded to the enhanced areas that were not ablated seen on CT.…”
Section: Discussionsupporting
confidence: 91%
“…It is an innovative software US technique specifically designed for imaging very low flow states, which uses a unique algorithm that allows for the visualization of diminutive vessels at slow velocity without using a contrast agent [ 9 ]. To date, although SMI has been used to detect blood flow signals in various serious clinical conditions (mainly in breast lesions [ 9 , 10 , 11 ]), as far as we know, no clinical research using SMI has been reported in muscle blood flow studies in critically ill patients with neuromuscular damage due to secondary sarcopenia associated with ICUAW. We found that around half of the studied patients had significantly lower QRF muscle microvascular angiogenic activity, as detected by SMI, than the control patients, who had normal vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Superb microvascular imaging (SMI) is an innovative US technique specifically designed for imaging very low-flow states, which uses a unique algorithm that allows for the visualization of diminutive vessels with slow velocity without using a sonographic contrast agent [ 9 ]. To date, although SMI has been used to detect blood flow signals in various conditions such as breast lesions [ 9 ], lymph nodes [ 10 ] or carcinomas [ 11 ], as far as we know, no clinical research with SMI technology for microvascular assessment has previously been reported in muscle blood flow studies in critically ill patients with neuromuscular secondary sarcopenia associated with ICUAW.…”
Section: Introductionmentioning
confidence: 99%
“…Adler grading [ 9 , 10 ] was used to classify Doppler blood flow in the tumour as follows: Adler 0 refers to that no obvious blood flow signal; Adler I refers to 1 or 2 small blood vessels with a diameter of 1 mm are detected; Adler II refers to that 3 or 4 small blood vessels are detected; Adler III refers to that more than 4 blood vessels, or the blood vessels are intertwined into a network are detected.…”
Section: Methodsmentioning
confidence: 99%